Proton versus photon radiation therapy for patients with high‐risk neuroblastoma: The need for a customized approach. Issue 10 (4th June 2013) - Hill‐Kayser, Christine; Tochner, Zelig; Both, Stefan; Lustig, Robert; Reilly, Anne; Balamuth, Naomi; Womer, Richard; Maris, John; Grupp, Stephen; Bagatell, Rochelle
Abstract Background Proton therapy for treatment for high‐risk neuroblastoma may offer sparing of organs at risk (OAR) when compared to intensity‐modulated X‐ray therapy (IMXT). Procedure Double‐scattered proton plans and IMXT plans delivering 2, 160 cGy to the primary tumor site and other residual disease were developed for 13 consecutive HR‐NBL patients. Radiation doses to target volumes and OAR were calculated to determine the optimal modality for each. Results All patients received radiation (5/13 ≥ 2 sites). No patient has experienced local recurrence or clinical organ toxicity. Coverage was excellent using both protons and IMXT: median % dose delivered to 95% clinical target volume was 99% and 100%, respectively. For nine patients with lateralized disease, proton therapy offered sparing of the contralateral kidney both with regard to median dose and dose to 20% (median <1 cGy vs. 362 cGy, P = 0.01; median 100 cGy vs. 634 cGy, P = 0.02, respectively). Proton therapy did not reduce ipsilateral kidney dose, and for 2 select patients with lateralized disease IMXT improved overall bilateral renal sparing. Proton therapy improved median bowel (median 33 cGy vs. 590 cGy, P = 0.01), total body (median <1 cGy vs. 30 cGy, P = 0.15), and liver dose (median <1 cGy vs. 529, P < 0.001). When chest RT was required, proton therapy decreased median heart dose and mean lung dose. Conclusions For most patients (11/13), proton therapy offered the optimal combination of target coverage and organ sparing, and is a feasible treatment for HR‐NBL. We recommend a customized approach with careful evaluation of renal dosimetry; IMXT may be preferred for select patients. Pediatr Blood Cancer 2013;60:1606–1611. © 2013 Wiley Periodicals, Inc.